Menggali Potensi Wakaf Produktif Untuk Kesejahteraan Umat - Unun Roudlotul Janah (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2009)
This study aims to explore the potential of productive waqf as an Islamic economic instrument in realizing the welfare of the ummah. Using a qualitative method and a literature study approach as well as secondary data analysis, this study examines the concept, practice, and challenges of implementing productive waqf in Indonesia. The results show that productive waqf has great potential to support the economic development of the ummah, especially in the education, health, and economic empowerment sectors. However, challenges such as low waqf literacy, weak nadzir management, and limited technical regulations are still major obstacles. This study recommends increasing the capacity of waqf managers, regulatory support, and synergy between sharia financial institutions and waqf institutions so that the potential of productive waqf can be optimized in a sustainable manner.